2021
DOI: 10.1051/epjpv/2021011
|View full text |Cite
|
Sign up to set email alerts
|

A round Robin-Highliting on the passivating contact technology

Abstract: The aim of this work is to demonstrate the maturity of the TOPCon technology by conducting a round-robin on symmetrically processed lifetime samples in the leading European PV institutes EPFL, ISC, CEA-INES, ISFH, IMEC and Fraunhofer ISE within the H2020 funded project called HighLite. For all layers, dark saturation current-densities ranging between 2 and 10 fA/cm2 can be reported. Simultaneously, no metal induced recombination for the two lower sintering temperatures have been observed pointing towards a tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In a first step, a large round‐robin experiment involving five of the leading EU PV institutes was organized by Fraunhofer ISE to evaluate various tunnel oxide passivated contacts (TOPCon) layers prepared by plasma enhanced chemical vapor deposition (PECVD) or by low pressure chemical vapor deposition (LPCVD) and using various dielectric capping layers. For all the approaches, dark saturation current‐densities ranging between 2 and 10 fA/cm 2 as shown in Figure 5A and contact resistivities below 10 mΩ.cm 2 have been achieved 34 . Additional characterization based on scanning spreading resistance microscopy (SSRM) revealed that many of those optimized layers feature local regions of doping enhancement favoring current transport 35 .…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…In a first step, a large round‐robin experiment involving five of the leading EU PV institutes was organized by Fraunhofer ISE to evaluate various tunnel oxide passivated contacts (TOPCon) layers prepared by plasma enhanced chemical vapor deposition (PECVD) or by low pressure chemical vapor deposition (LPCVD) and using various dielectric capping layers. For all the approaches, dark saturation current‐densities ranging between 2 and 10 fA/cm 2 as shown in Figure 5A and contact resistivities below 10 mΩ.cm 2 have been achieved 34 . Additional characterization based on scanning spreading resistance microscopy (SSRM) revealed that many of those optimized layers feature local regions of doping enhancement favoring current transport 35 .…”
Section: Resultsmentioning
confidence: 94%
“…(A) Total dark saturation density J0 for TOPCon samples with (0.48 mm finger pitch) and without metallization (infinite finger pitch) for different set peak firing temperatures in the range of 815–855°C 34 . (B) Laser scanning microscope image of local p + poly‐Si finger surrounded by textured silicon surface produced by a novel laser crystallization step for maskless structuring of p + poly‐Si 24 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations